Presidential Term Limits, Constitutional Justice, and Eternity Clauses: Preventing Unconstitutional Constitutional Amendments in Indonesia - Haikal Arsalan; Rofi Aulia Rahman; Dinda Silviana Putri (Mimbar Keadilan, 2026)
Constitutional justice functions as a substantive mechanism to uphold constitutional supremacy, limit state power, and protect fundamental democratic values. In presidential systems, one of its most critical institutional expressions is the regulation of presidential term limits, which aims to prevent the concentration of executive authority and to ensure democratic leadership rotation. This article examines the relationship between presidential term limits, constitutional justice, and the doctrine of eternity clauses as a means of preventing unconstitutional constitutional amendments in Indonesia. The study aims to assess whether presidential term limits should be constitutionally entrenched as unamendable provisions in order to safeguard Indonesia’s post-authoritarian constitutional order. Employing normative legal research, this study applies conceptual and statutory approaches by analyzing constitutional theory, comparative constitutional practices, constitutional court decisions, and Indonesian constitutional provisions, particularly the 1945 Constitution and its amendments. The findings demonstrate that presidential term limits are frequently targeted through formally valid constitutional amendments that substantively erode democratic principles, illustrating the paradox of unconstitutional constitutional amendments. Comparative experiences from Latin America, Africa, and Europe reveal that the removal or extension of term limits systematically reinforces incumbency advantages and weakens checks and balances. In the Indonesian context, debates surrounding the possibility of extending presidential terms highlight the vulnerability of constitutional safeguards when amendment procedures are dominated by political majorities. This article argues that designating presidential term limits as an eternity clause—or at minimum treating them as a substantive constitutional principle subject to strict judicial protection—is essential to preserving constitutional justice. Such entrenchment would reinforce Indonesia’s constitutional identity, prevent the abuse of amendment powers, and ensure that constitutional change remains aligned with democratic accountability and the rule of law.